2020
DOI: 10.1111/1749-4877.12450
|View full text |Cite
|
Sign up to set email alerts
|

Effects of masting on seedling establishment of a rodent‐dispersed tree species in a warm‐temperate region, northern China

Abstract: Masting is an evolutionary strategy used by plants to promote seed survival and/or seed dispersal under animal predation, but its effects on seedling establishment in field condition are rarely tested by long‐term experiments incorporating combined effects of seed and animal abundance. Here, we tracked seed production, rodent‐mediated seed dispersal, and seedling establishment in Armeniaca sibirica from 2005 to 2014 in a warm‐temperate forest in northern China, and examined the effects of seed abundance and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 55 publications
(112 reference statements)
3
16
0
Order By: Relevance
“…In this study, the decrease in seed predation by vertebrates at the pre-dispersal stage and by rodents at the post-dispersal stage, as observed in mast years, was consistent with the past studies (Xiao & Huang, 2020;Xiao et al, 2017). Moreover, the mean newly germinated seedling density recruited during mast years was about twice that recorded during non-mast years, which is similar to observations made in previous studies (Xiao et al, 2013;Zhang et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, the decrease in seed predation by vertebrates at the pre-dispersal stage and by rodents at the post-dispersal stage, as observed in mast years, was consistent with the past studies (Xiao & Huang, 2020;Xiao et al, 2017). Moreover, the mean newly germinated seedling density recruited during mast years was about twice that recorded during non-mast years, which is similar to observations made in previous studies (Xiao et al, 2013;Zhang et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the decrease in seed predation by vertebrates at the pre‐dispersal stage and by rodents at the post‐dispersal stage, as observed in mast years, was consistent with the past studies (Xiao & Huang, 2020; Xiao et al., 2017). Moreover, the mean newly germinated seedling density recruited during mast years was about twice that recorded during non‐mast years, which is similar to observations made in previous studies (Xiao et al., 2013; Zhang et al., 2020). These results suggest that masting of C. fargesii benefits seeds escaping predation and seedling recruitment, to some extent, supporting the predator satiation hypothesis in relation to the economies of scale (Xiao et al., 2013; Zwolak, Bogdziewicz, Wróbel et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In particular, seed dispersal is a key life‐history stage in plants, during which seeds or diaspores rely on agents such as wind and animals to spread to suitable sites away from the parent plant. Various studies have demonstrated that animals, especially small rodents, play a vital role in seed dispersal and they affect the seed‐to‐seedling period of plant regeneration (Abe et al, 2006 ; Williams‐Linera et al, 2011 ; Yu et al, 2017 , 2018 ; Zhang et al, 2019 , 2020 ). Usually, rodents eat part of the food (plant seeds or fruits) immediately after finding it, and the other part is often left scattered by the trees or stored to obtain food during periods of shortage (Ma et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the field experiment was conducted in the non-mast year of Korean pine, this did not amplify the effect of the lack of food scarcity because these granivores aren't the forest specialist species and other alternative resources are also available to these predators, such as acorn (Quercus mongolica) and walnut (Juglans mandshurica) (Yang et al 2016). However, given the SDE will be different between non-mast years and mast years (Li et al 2017;Zwolak et al 2016;Zhang et al 2021), our studies should be run over more years in the future to illustrate that granivore-mediated Korean pine regeneration is inadequate to ensure the restoration of secondary forests into mixed broad-leaved Korean pine forests. Besides that, interspecific synchrony or asynchrony of seed rain plays a key role in the formation of animalmediated seed dispersal (Yang et al 2020;Yu et al 2020), and seed rain compositions may further affect the dispersal success of Korean pine.…”
Section: Study Limitationmentioning
confidence: 99%